2018
DOI: 10.1007/s12028-018-0599-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrographic Seizures in Patients with Acute Encephalitis

Abstract: Electrographic seizures occur in approximately 40% of patients with acute encephalitis. Low serum sodium, cortical imaging abnormalities, and on cEEG LPDs and background abnormalities are associated factors. The lack of association with short-term outcome suggests that with aggressive treatment, the clinical impact of electrographic seizures in encephalitis can be minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…As in other studies on acute encephalitides [30], we found that 36.6% (11/30) of our patients had SCSs, a much higher percentage than those observed in both the general epileptic population (5.3%) and TLE cases (8.3%) [31,32]. Seventy-five% of the recorded SCSs occurred during sleep, and about 90% were documented by means of AEEG.…”
Section: Discussionsupporting
confidence: 76%
“…As in other studies on acute encephalitides [30], we found that 36.6% (11/30) of our patients had SCSs, a much higher percentage than those observed in both the general epileptic population (5.3%) and TLE cases (8.3%) [31,32]. Seventy-five% of the recorded SCSs occurred during sleep, and about 90% were documented by means of AEEG.…”
Section: Discussionsupporting
confidence: 76%
“…Whilst previous literature has demonstrated that prior overt clinical seizures are the most prevalent risk factor for NCSE [6], our results suggest that autoimmune encephalitis might be as common as known epilepsy as the cause of NCSE. Whilst autoimmune encephalitis is a well-established cause of convulsive SE, there is now an increasing body of literature describing NCSE in the context of autoimmune encephalitis [7][8][9][10][11][12]. Autoimmune encephalitis is an increasingly recognised cause of encephalitis and over the last 10 years there has been a marked expansion in the range of antibodies identified [13].…”
Section: Discussionmentioning
confidence: 99%
“…"lateralized periodic discharges" [LPDs]) meist im Gebiet eines Temporallappens, seltener und dann oft unabhängig voneinander in Form sog. bi-LPDs [43,57].…”
Section: A Rolle Des Eeg Im Akuten Und Längerfristigen Management Der Aieunclassified